Relevance and fusion of a Greek myth in a drama of Horacio Rega Molina - Fraschini, Alfredo Eduardo (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In this paper a comparative analysis of the drama Polyphemus and pears of the elm, by Horacio Rega Molina, is developed with the classic sources of the myth of Polyphemus: the Homeric Odyssey, The Cyclops of Euripides, the Idyllsof Theocritus, the Virgilian Aeneid, the Metamorphosisof Ovid, and the Fable of Polyphemus and Galateaby Luis de Góngora y Argote. The Argentine author has made a rewriting of the myth through the fusion of the sources and has developed the action placing it in the Argentine plain in the first half of the 20th century. He has preserved the general characteristics of the central characters of the myth: Polyphemus, Odysseus / Ulysses, and Galatea, but he has described an evolution in them to show how in Argentina the races have been mixed to generate the typical Creole.
Keywords: myth; transposition; opposition; peasant; urban; autochthonous; foreigner